The Effects of Cold Water Immersion and Active Recovery on Molecular Factors That Regulate Growth and Remodeling of Skeletal Muscle After Resistance Exercise - Peake, Jonathan M.; Markworth, James F.; Cumming, Kristoffer Toldnes; Aas, Sigve N.; Roberts, Llion A.; Raastad, Truls; Cameron-Smith, David; Figueiredo, Vandre C. (Frontiers in Physiology, 2020)
Regular postexercise cooling attenuates muscle hypertrophy, yet its effects on the key molecular factors that regulate muscle growth and remodeling are not well characterized. In the present study, nine men performed unilateral lower-body resistance exercise on separate days. On one day, they immersed their legs in cold water (10 deg C) for 10 min after exercise. On the other day, they cycled at a low intensity for 10 min after exercise. Muscle biopsies were collected from the exercised leg before, 2, 24, and 48 h after exercise in both trials. These muscle samples were analyzed to evaluate changes in genes and proteins involved in muscle growth and remodeling. Muscle-specific RING finger 1 mRNA increased at 2 h after both trials (P<0.05), while insulin-like growth factor (IGF)-1 Ec, IGF-1 receptor, growth arrest and DNA damage-inducible protein 45, collagen type I alpha chain A, collagen type III alpha chain 1, laminin and tissue inhibitor of metallopeptidase 1 mRNA increased 24-48 h after both trials (P<0.05). By contrast, atrogin-1 mRNA decreased at all time points after both trials (P<0.05). Protein expression of tenascin C increased 2 h after the active recovery trial (P<0.05), whereas FoxO3a protein expression decreased after both trials (P<0.05). Myostatin mRNA and ubiquitin protein expression did not change after either trial. These responses did not differ significantly between the trials. The present findings suggest that regular cold water immersion attenuates muscle hypertrophy independently of changes in factors that regulate myogenesis, proteolysis and extracellular matrix remodeling in muscle after exercise.